Perbedaan Ekspresi Kebahasaan Laki-laki dan Perempuan dalam Mengulas Makanan pada Vlog Kuliner di Platform Youtube - Suryani, Diana Sri (Crises on Languages and Literature, 2025)
This study is a sociolinguistic analysis utilizing a qualitative descriptive approach. The objective is to describe the differences in how males and females express delicious tastes and review food, as well as the distinctions between formal and informal language varieties in culinary vlogs on YouTube. The data for this study were collected from six culinary vloggers: three females (Ria SW, Mgdalenaf, and Separuh Aku Lemak) and three males (Tanboy Kun, Nex Carlos, and Mamank Kuliner). The primary sources of data were three videos from each of these YouTube channels. The data were gathered using a listening and note-taking method. For data analysis, the study employed theories of language and gender proposed by Lakoff (1973), Maltz & Borker (2009), and Wardhaugh & Fuller (2015). The findings revealed notable differences in the language used by males and females when expressing delicious taste. Males tend to use the word "delicious" in a more vulgar manner, while females tend to be more polite. Additionally, men provide detailed and direct information in their food reviews, whereas women are more minimal and hesitant in their descriptions. Moreover, men frequently use informal pronouns to convey solidarity, while women opt for formal pronouns and demonstrate greater politeness when reviewing food in their culinary vlogs.